Correlation between glycemic parameters and lipid profile in type 2 diabetic patients attending tertiary care centre in central region of Nepal - Sapkota, Lokendra Bahadur; Thapa, Sangita (Journal of Chitwan Medical College, 2017)
Background: Diabetes Mellitus (DM) is a chronic metabolic disease characterized by hyperglycemia with type 2 DM accounting for more than 90% of adult diabetes cases worldwide. Hyperglycemia in type 2 DM is strongly linked with dyslipidemia which in turn increases risk for development of cardiovascular diseases. This study aimed to determine the correlation between glycemic parameters (fasting blood sugar-FBS, postprandial blood sugar-PPBS and glycated hemoglobin-HbA1c) and serum lipid profile in type 2 diabetic patients. Methods: Altogether 160 type 2 diabetic patients (Male=80 and Female=80) aged between 30-70 years visiting Chitwan Medical College Teaching Hospital (CMCTH) for their routine medical check-up were included in this study. Data were collected using preformed set of questionnaires and biochemical data were obtained from the laboratory analysis of the patient’s blood samples. Statistical analysis was done with SPSS version 20.0. Results: Hyperglycemia was significant as evident by elevated FBS, PPBS and HbA1c. Also, the serum lipid profile was deranged with elevated TC, TG, LDL, VLDL and lowered HDL levels suggestive of dyslipidemia. There was a Direct and significant correlation of glycemic parameters (FBS, PPBS and HbA1c) with total cholesterol (TC), triglyceride (TG), low density lipoprotein cholesterol (LDL-C) and very low density lipoprotein cholesterol (VLDL-C) while the correlation with high density lipoprotein cholesterol (HDL-C) was just reverse. Conclusion: Chronic hyperglycemia in type 2 DM is associated with dyslipidemia which further exposes risk for the development of cardiovascular diseases. HbA1c, being the gold standard for the assessment of glycaemia is also the better predictor of dyslipidemia in type 2 diabetic patients.